(untitled) - Shier, David (Boston, 2000)
This full-color manual is designed for students with minimal backgrounds in the physical and biological sciences who are pursuing careers in allied health fields. Designed to supplement the seventh edition of Hole's Essentials of Human A&P by Shier, Butler, and Lewis, this one-semester manual contains 47 laboratory exercises and reports, which are integrated closely to the textbook. Exercises are planned to illustrate and review the anatomical and physiological facts and principles presented in the text and to help students investigate some of these ideas in greater detail.
Keywords: Human physiology,Human anatomy,Sinh lý người,Giải phẩu người